Vessel state and immune infiltration of the angiogenesis subgroup and construction of a prediction model in osteosarcoma - Wu, Jintao; Jin, Zhijian; Lin, Jianwei; Fu, Yucheng; Wang, Jun; Shen, Yuhui (Frontiers in Immunology, 2022)
Angiogenesis has been recognized as a pivotal contributor to tumorigenesis and progression. However, the role of angiogenesis-related genes (ARGs) in vessel state, immune infiltration and prognosis remains unknown in osteosarcoma (OS). Bulk RNA sequencing data of osteosarcoma patients was obtained from Therapeutically Applicable Research to Generate Effective Treatments (TARGET) database and patients were divided into two angiogenesis subgroups according to the expression of ARGs. We compared their vessel state and used two independent algorithms to evaluate tumor microenvironment (TME) in two subgroups. Furthermore, hub genes of differentially expressed genes (DEGs) in two subgroups were selected to perform LASSO regression and multivariate Cox stepwise regression, two prognostic hub genes were found. An ARG_score based on prognostic hub genes was calculated and proved to be reliable in overall survival prediction in OS patients. What is more, ARG_score was significantly associated with ARGs, immune infiltration, response to immunotherapy and drug sensitivity. To make our prediction model perform well, clinical features were added and a highly accurate interactive nomogram was constructed. Immunohistochemistry and qRT-PCR were utilized to verify the expression of prognostic hub genes. GSE21257 from Gene Expression Omnibus (GEO) database was used as a validation dataset to verify its robustness. In conclusion, our comprehensive analysis of angiogenesis subgroups in OS illustrated that angiogenesis may lead to different vessel state and further affect immune infiltration and prognosis of OS patients. Our findings may bring a novel perspective for the immunotherapy strategies for OS patients.